The Many Faces of Xenopus: Xenopus laevis as a Model System to Study Wolf–Hirschhorn Syndrome - Lasser, Micaela; Pratt, Benjamin; Monahan, Connor; Kim, Seung Woo; Lowery, Laura Anne (Frontiers in Physiology, 2019)
Wolf-Hirschhorn syndrome (WHS) is a rare developmental disorder characterized by intellectual disability and various physical malformations including craniofacial, skeletal, and cardiac defects. These phenotypes, as they involve structures that are derived from the cranial neural crest, suggest that WHS may be associated with abnormalities in neural crest cell (NCC) migration. This syndrome is linked with assorted mutations on the short arm of chromosome 4, most notably the microdeletion of a critical genomic region containing several candidate genes. However, the functions of these genes during embryonic development, as well as the cellular and molecular mechanisms underlying the disorder are still unknown. The model organism Xenopus laevis offers a number of advantages for studying WHS. With the Xenopus genome sequenced, genetic manipulation strategies can be readily designed in order to alter the dosage of the WHS candidate genes. Moreover, a variety of assays are available for use in Xenopus to examine how manipulation of WHS genes leads to changes in the development of tissue and organ systems affected in WHS. In this review article, we highlight the benefits of using Xenopus laevis as a model system for studying human genetic disorders of development, with a focus on WHS.